Operation analysis of the tele-critical care service demonstrates value delivery, service adaptation over time, and distress among tele-providers - Laudanski, Krzysztof; Huffenberger, Ann Marie; Scott, Michael J.; Williams, Maria; Wain, Justin; Jablonski, Juliane; Hanson, C. William (Frontiers in Medicine, 2022)
Background Our study addresses the gaps in knowledge of the characterizations of operations by remote tele-critical care medicine (tele-CCM) service providers interacting with the bedside team. The duration of engagements, the evolution of the tele-CCM service over time, and the distress during interactions with the bedside team have not been characterized systematically. These characteristics are critical for planning the deployment of teleICU services and preventing burnout among remote teleICU providers. Methods REDCap self-reported activity logs collected engagement duration, triggers (emergency button, tele-CCM software platform, autonomous algorithm, asymmetrical communication platform, phone), expediency, nature (proactive rounding, predetermined task, response to medical needs), communication modes, and acceptance. Seven hospitals with 16 ICUs were overseen between 9/2020 and 9/2021 by teams consisting of telemedicine medical doctors (eMD), telemedicine registered nurses (eRN), and telemedicine respiratory therapists (eRT). Results 39,915 total engagements were registered. eMDs had a significantly higher percentage of emergent and urgent engagements (31.9%) vs. eRN (9.8%) or eRT (1.7%). The average tele-CCM intervention took 16.1 ± 10.39 min for eMD, 18.1 ± 16.23 for eRN, and 8.2 ± 4.98 min for eRT, significantly varied between engagement, and expediency, hospitals, and ICUs types. During the observation period, there was a shift in intervention triggers with an increase in autonomous algorithmic ARDS detection concomitant with predominant utilization of asynchronous communication, phone engagements, and the tele-CCM module of electronic medical records at the expense of the share of proactive rounding. eRT communicated more frequently with bedside staff (% MD = 37.8%; % RN = 36.8, % RT = 49.0%) but mostly with other eRTs. In contrast, the eMD communicated with all ICU stakeholders while the eRN communicated chiefly with other RN and house staff at the patient's bedside. The rate of distress reported by tele-CCM staff was 2% among all interactions, with the entity hospital being the dominant factor. Conclusions Delivery of tele-CCM services has to be tailored to the specific beneficiary of tele-CCM services to optimize care delivery and minimize distress. In addition, the duration of the average intervention must be considered while creating an efficient workflow.